2005
DOI: 10.1080/03079450500059461
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellaprofile in chickens determined by real-time polymerase chain reaction and bacteriology from years 2000 to 2003 in Turkey

Abstract: From years 2000 to 2003, Salmonella was investigated from a total of 1785 samples comprised of chicken intestinal samples, cloacal swabs, drag swabs, litter samples and chick dust samples collected from 191 poultry breeding flocks belonging to 15 different chicken breeding stock companies in the Marmara region, Turkey by a SYBR green-based real-time polymerase chain reaction (SGBRT-PCR), by a probe-specific real-time polymerase chain reaction (PSRT-PCR) and by standardized bacteriology as described in the manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
4
6
1
Order By: Relevance
“…This leads to the conclusion that the use of cecal swab and intestine samples in Salmonella detection would yield reliable results. In this study, the Salmonella detection rate of rPCR was higher than ISO culture except for intestine samples, which is almost in parallel to our previous findings (Eyigor and Carli, 2003;Eyigor et al, 2005). The false-positive results in rPCR were also observed by Bohaychuk et al (2007) andO'Regan et al (2008).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This leads to the conclusion that the use of cecal swab and intestine samples in Salmonella detection would yield reliable results. In this study, the Salmonella detection rate of rPCR was higher than ISO culture except for intestine samples, which is almost in parallel to our previous findings (Eyigor and Carli, 2003;Eyigor et al, 2005). The false-positive results in rPCR were also observed by Bohaychuk et al (2007) andO'Regan et al (2008).…”
Section: Discussionsupporting
confidence: 87%
“…Apart from the effects of Salmonella prevalence within a flock (Arnold et al, 2010), of the housing system (Carrique-Mas et al, 2009;Huneau-Salaün et al, 2009), and of the flock characteristics (Namata et al, 2008), the variations in Salmonella detection rates have particularly been re- I 0 3 0 34 II 30 4 1 0 III 93 3 0 16 IV 11 13 8 4 V 1 0 0 27 VI 0 0 0 11 Total 135 23 9 92 lated to the sample type analyzed and the method used (Rybolt et al, 2004;Kinde et al, 2005;Arnold et al, 2010). In this study for instance, cecal swab and intestine samples, as supported by former study data (Nief and Hoop, 1998;Kalender and Muz, 1999;Carli et al, 2001b;Eyigor and Carli, 2003;Eyigor et al, 2005;Ata and Aydın, 2008) seemed to work relatively better for Salmonella detection both by rPCR and ISO culture than other sample types, such as cloacal swabs. This leads to the conclusion that the use of cecal swab and intestine samples in Salmonella detection would yield reliable results.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…To determine the causative agent of this disease, we first investigated several pathogens that had previously been reported to associate with infectious synovitis in broiler chickens by pathogenic detection, including Salmonella [16] , Reovirus [17, 18] , Streptococcus [19, 20] , Staphylococcus [21] , and M. synoviae [2] . The results indicated that no of these pathogens could be detected (data not shown).…”
Section: Resultsmentioning
confidence: 99%